Undelivered constitutional justice? Study on how the decisions of the Constitutional Court of the Republic of Indonesia are executed - Hasani, Ismail; Halili, Halili; Balakrishnan, Vishalache (Universitas Negeri Yogyakarta, 2022)
The constitutional design of the institution of the Constitutional Court (MK), as the guardian and the sole interpreter of the Constitution, is to ensure and guarantee the supremacy of the Constitution, constitutional compliance, and to bestow constitutional justice for citizens in the practice of Indonesian administration. However, the reality of the Indonesian state administration shows that there is still disobedience or neglect of the judicial review decision produced by the Constitutional Court. This paper aims to analyze how the Constitutional Court's decision is executed and offer the alternatives to overcome non-compliance with the decision or ensure follow-up on the Constitutional Court's decision in the judicial reviews. This research is normative legal research using a statutory approach, comparison, and conceptual approach. This study's results indicate a constitutional evil in the form of neglect or disobedience to the decision. In that context, institutional improvements that can be adopted are needed to strengthen collective adherence to the supremacy of the Constitution. The three alternatives offered by this article are the amendment of the Constitution, the granting of flexibility to the PUU of the Constitutional Court, and the establishment of a Special Directorate at the Ministry of Law and Human Rights